athematic progression

Asked by  | 22nd Dec, 2009, 02:45: PM

Expert Answer:

1/ We can find the common difference = second term - first term = q-p

Last term = p + (n-1)d = p + (n-1)(q-p) = 2p

Hence n = q/(q-p)

Sum = n(first term + last term)/2 = q(p + 2p)/(q-p) = 3pq/(q-p)

In case of multiple questions within a query, please post each question individually and let us know where you are getting stuck so that we would be able to explain things better.




Answered by  | 22nd Dec, 2009, 03:44: PM

Queries asked on Sunday & after 7pm from Monday to Saturday will be answered after 12pm the next working day.